2023
DOI: 10.12669/pjms.39.2.6901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Butylphthalide combined with Oxiracetam on cognitive function, Intellectual recovery and serum inflammatory factors in patients with cognitive impairment after cerebral infarction

Abstract: Objective: To evaluate the effect of butylphthalide combined with oxiracetam on cognitive function, intellectual recovery and serum inflammatory factors in patients with cognitive impairment after cerebral infarction. Methods: This is a Clinical comparative study. A total of 80 patients with cognitive impairment after cerebral infarction who visited Renmin Hospital, Hubei University of Medicine from January 2020 to January 2022 were enrolled and randomly divided into two groups. Patients in the control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In a clinical study, Jimbo et al (2009) used aromatherapy to treat 28 patients with dementia with rose-lemon EO in the morning and lavender-Orange peel EO in the evening and found that the essential oil group had a better sense of cognitively relevant spatial orientation compared to the control group. Wang (2014) observed the intervention effect of rosemary inhalation and sniffing method in patients with CI after cerebral infarction, and the results showed that conventional rehabilitation therapy combined with rosemary inhalation and sniffing had the immediate efficacy of improving cognitive function and activities of daily living in patients with CI after cerebral infarction and improving the effectiveness of rehabilitation therapy.…”
Section: Advantages Of Volatile Oil In the Treatment Of Cognitive Dis...mentioning
confidence: 99%
“…In a clinical study, Jimbo et al (2009) used aromatherapy to treat 28 patients with dementia with rose-lemon EO in the morning and lavender-Orange peel EO in the evening and found that the essential oil group had a better sense of cognitively relevant spatial orientation compared to the control group. Wang (2014) observed the intervention effect of rosemary inhalation and sniffing method in patients with CI after cerebral infarction, and the results showed that conventional rehabilitation therapy combined with rosemary inhalation and sniffing had the immediate efficacy of improving cognitive function and activities of daily living in patients with CI after cerebral infarction and improving the effectiveness of rehabilitation therapy.…”
Section: Advantages Of Volatile Oil In the Treatment Of Cognitive Dis...mentioning
confidence: 99%
“…Other brain cytoprotective therapies were considered as Grade IIb recommendations [ 5 ]. DI-3-n-butylphthalide (NBP) is a drug developed independently in China that acts on multiple pathological links of acute ischemic stroke [ 8 ] and was approved for treatment of AIS by the NMPA in 2010. Clinical studies have demonstrated that NBP can improve the oxidative stress response of the nervous system [ 9 ], inhibit neuronal apoptosis and autophagy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%